Dynamic impact experiment and response characteristics analysis for 1:2 reduced-scale model of hydraulic support - Ren, Huaiwei; Zhang, Desheng; Gong, Shixin; Zhou, Kai; Xi, Chenyang; He, Ming; Li, Tijian (International journal of mining science and technology, 2021)
It is significant to research the impact resistance properties of hydraulic support due to its key support role in the fully mechanized mining face. However, it is difficult for the entire hydraulic support to implement the impact experiment underground and analyze the response characteristic. Therefore, a dynamic impact experiment for the entire hydraulic support was proposed in this paper, where a 1:2 reduced-scale model of hydraulic support was designed and its response characteristics under dynamic impact load were analyzed. Firstly, a comprehensive monitoring scheme was proposed to achieve an effective monitoring for dynamic response of hydraulic support. Secondly, a multi-scale impact experiment was carried out for the entire hydraulic support and dynamic behaviors of hydraulic support under the multi-scale impact load were revealed by experimental data. Then a dynamic impact experiment of the entire hydraulic support was simulated in ADAMS with the same experiment conditions, and the experimental and simulation data were verified mutually. Finally, the characteristics of energy conversion and dissipation of the entire experiment system after impact were analyzed. The experiment results showed that the impact resistance properties of hydraulic support largely depended on the initial support conditions and different vertical rigidities affected energy distribution proportion of the entire support system.